Behavior of two-chamber microbial electrochemical systems started-up with different ion-exchange membrane separators. (April 2019) - Koók, László; Quéméner, Elie Desmond-Le; Bakonyi, Péter; Zitka, Jan; Trably, Eric; Tóth, Gábor; Pavlovec, Lukas; Pientka, Zbynek; Bernet, Nicolas; Bélafi-Bakó, Katalin; Nemestóthy, Nándor
Highlights: The use of certain anion/cation exchange membranes in MFC is first presented. The type of membrane separator affected the efficiency of MFC start-up. MFC with anion exchange membrane showed outstanding performance. Geobacter was dominantly selected on anodes independently of membrane type. Voltammograms indicated various anode surface coverage of redox components. Abstract: In this study, microbial fuel cells (MFCs) – operated with novel cation- and anion-exchange membranes, in particular AN-VPA 60 (CEM) and PSEBS DABCO (AEM) – were assessed comparatively with Nafion proton exchange membrane (PEM). The process characterization involved versatile electrochemical (polarization, electrochemical impedance spectroscopy – EIS, cyclic voltammetry – CV) and biological (microbial structure analysis) methods in order to reveal the influence of membrane-type during start-up. In fact, the use of AEM led to 2–5 times higher energy yields than CEM and PEM and the lowest MFC internal resistance (148 ± 17 Ω) by the end of start-up. Regardless of the membrane-type, Geobacter was dominantly enriched on all anodes. Besides, CV and EIS measurements implied higher anode surface coverage of redox compounds for MFCs and lower membrane resistance with AEM, respectively. As a result, AEM based on PSEBS DABCO could be found as a promising material to substitute Nafion.